Desempenho produtivo de vacas leiteiras simental suplementadas com ácido ricinoleico extraido do óleo de mamona - Gandra, J. R.; Nunes Gil, P. C.; Gandra, E. R.S.; Del, Vale T.A.; Barletta, R. V.; Zanferari, F.; Ferreira de Jesus, E. [UNESP]; Takiya, C. S.; Mingoti, R. D.; Almeida, G. F.; Paiva, P. G. [UNESP]; Gobesso, A. (SciELO Espana/Repisalud, 2014)
The aim of this study was to evaluate the performance and blood parameters of Simmental dairy cows, supplemented with 2 g/day of ricinoleic acid (RA) in diet. Forty Simmental dairy cows in mid lactation, individually housed in stable type tiestall, were used. The animals were randomly assigned to two treatments: 0 or 2 g of RA/animal/day. The experimental period consisted of 42 days divided into two 21-day. It was observed reduction in dry matter intake (DMI), increased milk, fat and FCM (fat corrected milk) yield, as well as increased of fat content of milk in cows that received RA in diets. No effects were observed for red and white blood cells and blood metabolites. Supplementation of RA improves performance of dairy cows in mid lactation.
Productive performance of simmental dairy cows supplemented with ricinoleic acid from castor oil
Keywords: Blood cells; Functional oil; Milk yield; Plasma metabolites